2012
DOI: 10.5114/jcb.2012.30683
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an eye on the ring: COMS plaque loading optimization for improved dose conformity and homogeneity

Abstract: PurposeTo improve tumor dose conformity and homogeneity for COMS plaque brachytherapy by investigating the dosimetric effects of varying component source ring radionuclides and source strengths.Material and methodsThe MCNP5 Monte Carlo (MC) radiation transport code was used to simulate plaque heterogeneity-corrected dose distributions for individually-activated source rings of 14, 16 and 18 mm diameter COMS plaques, populated with 103Pd, 125I and 131Cs sources. Ellipsoidal tumors were contoured for each plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Doses delivered to critical ocular structures within the eye model, normalized in terms of dose to the tumor apex, are generally lowest for 103 Pd and highest for 131 Cs, with the exception of the tumor where average doses are comparable for 125 I and 103 Pd, and are lowest for 131 Cs. These observations have previously been reported for a water-equivalent eye [46][47][48] and have been shown in this work to hold when ocular media are considered, although specific comparison of doses delivered with the different radionuclides are sensitive to the simulation geometry.…”
Section: Resultssupporting
confidence: 80%
“…Doses delivered to critical ocular structures within the eye model, normalized in terms of dose to the tumor apex, are generally lowest for 103 Pd and highest for 131 Cs, with the exception of the tumor where average doses are comparable for 125 I and 103 Pd, and are lowest for 131 Cs. These observations have previously been reported for a water-equivalent eye [46][47][48] and have been shown in this work to hold when ocular media are considered, although specific comparison of doses delivered with the different radionuclides are sensitive to the simulation geometry.…”
Section: Resultssupporting
confidence: 80%
“…Plaque arrangements can vary in source strengths and ring sizes [ 33 ]. An independent check of treatment time by redundant calculation was performed.…”
Section: Methodsmentioning
confidence: 99%
“…COMS plaques may be used in a non‐standard way: for example, the gold alloy plaque backing alone with no Silastic insert and seeds directly affixed to the plaque backing, with a very thin reusable seed‐guide insert, or with non‐uniform loading to improve homogeneity of the dose distribution . In 2005, Astrahan et al reported a dosimetry study that used the Plaque Simulator © treatment planning system (Eye Physics, LLC, Los Alamitos, CA) to calculate dose distributions for the COMS plaque backing with the 0.3 mm thick gold alloy seed guide.…”
Section: Review Of Dosimetric Studies For Various Plaque Modelsmentioning
confidence: 99%